Estimation of Primary and Scatter Signal Profiles in Computer Tomography using Geant4 - Arroyo Portilla, Daniel José (2024)
A method to obtain the scatter signal profiles from a commercially available computer tomography scanner, using Geant4 a Monte Carlo toolkit for C++ to create a code that mimics the most important structures of the scanner, like the bowtie filter, detecting el- ements and septa. A uniform water phantom with different diameters can be placed at the isocenter to study the scatter generated and the attenuation of the signal in the de- tecting structure. The signal characterization algorithm finds the last photon interaction before reaching a detecting element to assign based on the volume scatter profiles. Simulations without the phantom show that the crosstalk signal is between 1% and 2% of the total signal for both source energies and collimations, the septa scatter signal is lower but at the edges of each detecting module surpassing the bowtie and air signal contributions, the bowtie signal is about 0.1% of the air scan in the central module and up to 2% when moving away from the center of the detecting structure. Simulations with the phantom present show a total attenuation in the detecting struc- ture of from 2% for the smaller phantom up to 0.14% for the biggest one. Phantom scat- ter varies with the source energy and collimation, contributing up to 5% with a 320mm diameter phantom. Normalized scatter profiles can help to understand the effect of the phantom signal in a projection, simulations with all the scanner structures present and simulations where the bowtie and/or anti-scatter grid is missing can show the impact of the structures when it comes to reducing the scatter signal. Also, small signal contributions from the scanner structures and the air can be identified and assessed to see the impact on the total signal. The code developed successfully mimics the scatter signal of a CT scanner and separates it into the different scatter sources from the phantom to the scanner structures and air.